EVALUATION OF THE ANTI-ARTHRITIC ACTIVITY OF THE AQUEOUS EXTRACT OF THE LEAVES OF ANNONA SENEGALENSIS PERS. (ANNONACEAE) - IGNACE KOUSSOUBÉ; FILKPIÈRÈ LÉONARD DA; BASILE TINDANO; PATÉNÉMA SAWADOGO; ALBERT SOUDRÉ (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: Rheumatoid arthritis (RA) is a chronic inflammatory disease affecting the joints, with symptoms such as edema, pain, and joint deformities. This study aimed to evaluate the effect of the aqueous extract of the leaves of Annona senegalensis on arthritis in rats. Methods: Arthritis was induced by injecting 0.1 mL of Complete Freund’s Adjuvant (CFA) into the left hind paw of the rats. The extract was administered orally at daily doses of 40, 100, and 200 mg/kg body weight. Assessments included paw edema volume, joint structure, oxidative stress markers, and the activity of major antioxidant enzymes. Preliminary phytochemical analysis showed significant levels of polyphenols (224.71±8.42 mg EAG/g extract), flavonoids (26.16±2.09 mg EQ/g extract), and tannins (107.06±5.19 mg EAT/g). The extract significantly reduced paw edema volume (p<0.001), with inhibition rates reaching up to 44.74%. Biochemical analyses showed a reduction in oxidative stress, indicated by decreased malondialdehyde levels and increased activities of antioxidant enzymes, particularly superoxide dismutase and catalase. Histological examination of paw tissue from treated and control animals showed improved joint architecture following extract administration. Conclusion: A. senegalensis exhibits significant anti-arthritic potential, supporting its use as a promising therapeutic agent for the management of RA.